Applications of Chitosan and its Derivatives in Skin and Soft Tissue Diseases - Xia, Yidan; Wang, Dongxu; Liu, Da; Su, Jiayang; Jin, Ye; Wang, Duo; Han, Beibei; Jiang, Ziping; Liu, Bin (Frontiers in Bioengineering and Biotechnology, 2022)
Chitosan and its derivatives are bioactive molecules that have recently been used in various fields, especially in the medical field. The antibacterial, antitumor, and immunomodulatory properties of chitosan have been extensively studied. Chitosan can be used as a drug-delivery carrier in the form of hydrogels, sponges, microspheres, nanoparticles, and thin films to treat diseases, especially those of the skin and soft tissue such as injuries and lesions of the skin, muscles, blood vessels, and nerves. Chitosan can prevent and also treat soft tissue diseases by exerting diverse biological effects such as antibacterial, antitumor, antioxidant, and tissue regeneration effects. Owing to its antitumor properties, chitosan can be used as a targeted therapy to treat soft tissue tumors. Moreover, owing to its antibacterial and antioxidant properties, chitosan can be used in the prevention and treatment of soft tissue infections. Chitosan can stop the bleeding of open wounds by promoting platelet agglutination. It can also promote the regeneration of soft tissues such as the skin, muscles, and nerves. Drug-delivery carriers containing chitosan can be used as wound dressings to promote wound healing. This review focuses on the application of chitosan and its derivatives in soft tissue diseases. The structure and biological characteristics of chitosan and its derivatives, and their therapeutic effects on soft tissue diseases have been elaborated when used as different drug-delivery carriers, highlighting their applications in a clinical setting.